ASSESSMENT OF INTEGRATED PEST MANAGEMENT MODULES FOR THE MANAGEMENT OF GRAPE MEALY BUG, MACONELLICOCCUS HIRSUTUS (GREEN) - VINAYKUMAR M. M.; GOPALI J. B.; VENKATESHALU; NADAF A. M. (The Bioscan, 2019)
The pink hibiscus mealy bug Maconellicoccus hirsutus (Green) is a serious pest of the grape vine. High incidence of this pest was observed in the grape vineyards resulted in a poor fruit quality. During April pruning the chemo- intensive module has shown most effective against the mealy bug individuals and recorded lowest (2.41/ colony) mealy bug population, whereas, in adaptable module (2.54 mealy bug/colony) and biological module (3.83 mealy bug/colony) has recorded moderately higher mealy bugs per colony as compared to untreated check (i.e., 3.96 mealy bug/colony). Similarly, during October pruning the lowest egg mass (4.25/vine), mealy bug individual (3.36/colony) and mealy bug colonies (5.55/vine) were observed in Chemo-intensive module. Further, highest B: C ratio was obtained from Adaptable module (4.97) with a net return of Rs. 633450. Among the different modules, adaptable module is found superior due to economically and environmentally safer to protect the crop from insect pests.